2013
DOI: 10.1144/jgs2013-030
|View full text |Cite
|
Sign up to set email alerts
|

Hot rocks in a cold place: high sub-glacial heat flow in East Antarctica

Abstract: Numerical models are the primary predictive tools for understanding the dynamic behavior of the Antarctic ice sheet. But a key boundary parameter -sub-glacial heat flow -remains poorly constrained. We show that variations in abundance and distribution of heat-producing elements within the Antarctic continental crust result in greater and more variable regional sub-glacial heat flows than currently assumed in ice modeling studies. Such elevated heat flows would fundamentally impact on ice sheet behaviour and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 27 publications
8
95
2
Order By: Relevance
“…As a group they are distinctly different from the regional pattern shown by anomalously warm Proterozoic crust in central Australia with average q o = 80 mW m −2 (McLaren et al, 2003), which has been suggested to extend across the Wilkes Land margin of Antarctica based on Gondwana supercontinent reconstructions (Carson et al, 2014;Aitken et al, 2014). Despite general age similarities among some of the clast population with parts of the Gawler Craton, and basement age correlations that indicate continuity of Mawson-type crust into the Wilkes sector of East Antarctica (Goodge and Fanning, 2016), the proxy heat production determinations and heat flow estimates provided here suggest that central portions of the East Antarctic ice sheet are underlain by stable continental crust with quite normal thermal properties represented by average values of heat production of about 2.5 µW m −3 and heat flow of about 50 mW m −2 .…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…As a group they are distinctly different from the regional pattern shown by anomalously warm Proterozoic crust in central Australia with average q o = 80 mW m −2 (McLaren et al, 2003), which has been suggested to extend across the Wilkes Land margin of Antarctica based on Gondwana supercontinent reconstructions (Carson et al, 2014;Aitken et al, 2014). Despite general age similarities among some of the clast population with parts of the Gawler Craton, and basement age correlations that indicate continuity of Mawson-type crust into the Wilkes sector of East Antarctica (Goodge and Fanning, 2016), the proxy heat production determinations and heat flow estimates provided here suggest that central portions of the East Antarctic ice sheet are underlain by stable continental crust with quite normal thermal properties represented by average values of heat production of about 2.5 µW m −3 and heat flow of about 50 mW m −2 .…”
Section: Discussioncontrasting
confidence: 62%
“…from Archean and Paleoproterozoic bedrock exposed in the coastal region of southern Prydz Bay (2.4-2.6 µW m −3 ; Carson and Pittard, 2012; Carson et al, 2014). Four of the clasts give high values between 4.0 and 7.5 µW m −3 , which are similar to global occurrences of crust characterized by high heat production (Mareschal and Jaupart, 2013;Jaupart et al, 2016) and exemplified by the Central Australian Heat Flow Province (Neumann et al, 2000;Sandiford and McLaren, 2002;McLaren et al, 2003).…”
Section: Heat Productionmentioning
confidence: 83%
See 3 more Smart Citations